On the size and velocity distribution of cosmic dust particles entering the atmosphere - Carrillo‐Sánchez, J. D. (Geophys Res Lett, 2015)
The size and velocity distribution of cosmic dust particles entering the Earth's atmosphere is uncertain. Here we show that the relative concentrations of metal atoms in the upper mesosphere, and the surface accretion rate of cosmic spherules, provide sensitive probes of this distribution. Three cosmic dust models are selected as case studies: two are astronomical models, the first constrained by infrared observations of the Zodiacal Dust Cloud and the second by radar observations of meteor head echoes; the third model is based on measurements made with a spaceborne dust detector. For each model, a Monte Carlo sampling method combined with a chemical ablation model is used to predict the ablation rates of Na, K, Fe, Mg, and Ca above 60 km and cosmic spherule production rate. It appears that a significant fraction of the cosmic dust consists of small (<5 µg) and slow (<15 km s(−1)) particles.